Effects of breastfeeding education based on the self-efficacy theory on women with gestational diabetes mellitus: A CONSORT-compliant randomized controlled trial. Issue 16 (April 2020) - You, Huaxuan; Lei, Anjiang; Xiang, Jie; Wang, Yan; Luo, Biru; Hu, Juan
Abstract: Background: Women with gestational diabetes mellitus (GDM) face big challenges of breastfeeding. In order to improve breastfeeding self-efficacy and breastfeeding rate of them, we formulated perinatal individualized interventions based on self-efficacy theory and conducted a randomized controlled trial to verify the effectiveness. Methods: We conducted a randomized controlled trial. The perinatal individualized interventions based on the self-efficacy theory including 4 phases were led by the International Board Certified Lactation Consultant (IBCLC). Women allocated to the control group received usual care for lactation support during the antenatal and postnatal period. Data collection occurred at admission, discharge, 6 weeks postpartum, 4 months postpartum, and 6 months postpartum. Results: We enrolled 226 women with GDM, 113 in the intervention group and 113 in the control group. The scores of breastfeeding self-efficacy in the intervention group were significantly higher than those in the control group at discharge, at 6 weeks, 4 months, and 6 months postpartum ( P < .05). We found higher rates of exclusive and any breastfeeding in the intervention group at discharge (Exclusive: 25.2% vs 13.5%, P < .05; Any: 94.4% vs 89.4%, P > .05), at 6 weeks postpartum (Exclusive: 75.5% vs 62.5%, P < .05; Any: 100.0% vs 96.2%, P > .05), at 4 months postpartum (Exclusive: 68.9% vs 43.3%, P < .05; Any: 94.3% vs 83.7%, P < .05) and at 6 months postpartum (Exclusive: 55.8% vs 36.9%, P < .05; Any: 88.5% vs 64.1%, P < .05). Conclusion: Perinatal individualized breastfeeding education based on the self-efficacy theory had positive effects on breastfeeding self-efficacy and breastfeeding rate of women with GDM.